Varenicline Dose Dependently Enhances Responding for Nonpharmacological Reinforcers and Attenuates the Reinforcement-Enhancing Effects of Nicotine - Levin, Melissa E. (Oxford University Press, 2012)
INTRODUCTION: Varenicline (VAR), a partial nicotinic agonist, is one of the most effective smoking cessation pharmacotherapies. The therapeutic efficacy of VAR could be partly the result of substituting for and/or blocking the reinforcement-enhancing effects of nicotine (NIC). We assessed the effects of VAR alone and in combination with NIC (0.4 mg/kg) while rats pressed the lever for a moderately reinforcing visual stimulus (VS). METHODS: Rats were injected with placebo (0.9% saline), NIC, VAR (0.1–1 mg/kg), or NIC + VAR. A follow-up study was conducted with a broader dose range of VAR-alone dosages (0.01–3.0 mg/kg). All drug manipulations were conducted in a between-subjects design to prevent confounding effects of repeated exposure. RESULTS: There was a dose-dependent effect of VAR alone. Moderate doses of VAR (0.1 and 1.0 mg/kg) increased the number of VS presentations earned, while lower and higher VAR doses (0.01 and 3.0 mg/kg) did not change responding for the VS. VAR dose dependently attenuated the reinforcement-enhancing effects of NIC, with the highest dose (1.0 mg/kg) exhibiting the greatest antagonist effect. CONCLUSIONS: The results of these studies support the assertion that the therapeutic efficacy of VAR may be due to the partial agonist characteristics of the drug, specifically, its ability to partially replace the reinforcement-enhancing effects of NIC as well as antagonize these effects.